Does innovation strategy affect financial, social and environmental performance? - Ezzi, Ferdaws (2016)
In the very study the emphasis lays on the specific problem of analyzing the impact of the innovation strategy (in particular investment in research and development) on the financial social and environmental performance. After discussing this subject theoretically we propose our research hypotheses which in turn will be corroborated by an empirical study of 96 Tunisian companies. Indeed the results are noteworthy and important to the extent that one can say that the innovation strategy has a crucial impact on the performance of the companies.